Ramsey Pricing Revisited: Natural Monopoly Regulation with Evaders - Martin Besfamille; Nicolás Figueroa; Léon Guzmán (Center for Economic Studies and ifo Institute (CESifo), 2023)
We consider a model featuring a single-product natural monopoly, which faces evaders, i.e., individuals that may not pay the price. By exerting a costly effort, the firm can deter evasion. To maximize the total surplus, a regulator sets the price, the level of deterrence effort, and socially costly transfers to ensure the monopoly's participation. We obtain a modified Ramsey formula, which clearly shows that the mere existence of evaders dampens the use of the price as a mean to finance the firm's deficit. The regulated price is always below the monopoly price and, under sufficient conditions, also below marginal cost. Then, we generalize the model to incorporate moral hazard. Finally, we undertake an empirical application of our results, which shows quantitatively that the downward tendency of regulated prices in a context of high evasion is significant.
Keywords: D42; H20; L43; L51; 330; regulation; natural monopoly; evasion and marginal cost of public funds